Art with a difference : - Diepeveen, Leonard (McGraw-Hill, 2000)
Designed as a supplementary text for beginning art courses, this brief, inexpensive text introduces issues that are typically overlooked in standard art survey texts, such as the role of the museum in creating the canon, ways to understand art of other cultures and outsider art, and the difficulty many beginners have in understanding art, especially contemporary art.